Uji Daya Hambat Ekstrak Buah Nanas (Ananas comosus L.Merr.), Salak (Salacca edulis Reinw.) dan Mangga Kweni (Mangifera odorata Griff.) terhadap Daya Hambat Staphylococcus aureus - Endang Suerni; Muhammad Alwi; Musjaya M. Guli (Biocelebes, 2013)
The purpose of this research was to investigate whether the extract of some fruits: pineapple (Ananas comosus L.Merr.), bark (Salacca edulis Reinw.), and Kweni mango (Mangifera odorata Griff.) has antimicrobial against the bacteria and how effective is the extract of pineapple (Ananas comosus L.Merr.), bark (Salacca edulis Reinw.), and kweni mango (Mangifera odorata Griff.). The bacteria of Staphylococcus aureus examined its growth is the bacteria purified from the common skin decease, that is, inflamed pimple. This research used Factorial RAL Design and further tested by employing Duncan Multiple Range Test (DMRT). If is found that the extract of pineapple, bark, and kweni mango can inhibit the growth of Staphylococcus aureus bacteria. The greatest inhibiting zone was the inhibiting zone produced by the extract of mango (Mangifera odorata Griff.) under the concentration of 100%. Key words: The extract of pineapple, bark, mango; inhibiting power, Staphylococcus aureus.